Long‐term survival after endovascular and open repair of unruptured abdominal aortic aneurysm. Issue 13 (20th November 2019) - Johal, A. S.; Loftus, I. M.; Boyle, J. R.; Heikkila, K.; Waton, S.; Cromwell, D. A.
Abstract : Background: The aim of this study was to examine patterns of 10‐year survival after elective repair of unruptured abdominal aortic aneurysms (AAAs) in different patient groups. Methods: Patients having open repair or endovascular aneurysm repair (EVAR) in the English National Health Service between January 2006 and December 2015 were identified from Hospital Episode Statistics data. Postoperative survival among patients of different age and Royal College of Surgeons of England (RCS) modified Charlson co‐morbidity score profiles were analysed using flexible parametric survival models. The relationship between patient characteristics and risk of rupture after repair was also analysed. Results: Some 37 138 patients underwent elective AAA repair, of which 15 523 were open and 21 615 were endovascular. The 10‐year mortality rate was 38·1 per cent for patients aged under 70 years, and the survival trajectories for open repair and EVAR were similar when patients had no RCS‐modified Charlson co‐morbidity. Among older patients or those with co‐morbidity, the 10‐year mortality rate rose, exceeding 70 per cent for patients aged 80 years. Mean survival times over 10 years for open repair and EVAR were often similar in subgroups of older and more co‐morbid patients, but their survival trajectories became increasingly dissimilar, with open repair showing greater short‐term risk within 6 months but lower 10‐year mortality rates. The risk of rupture over 9 years was 3·4 per cent for EVAR and 0·9 per cent for open repair, and was weakly associated with patient factors. Conclusion: Long‐term survival patterns after elective open repair and EVAR for unruptured AAA vary markedly across patients with different age and co‐morbidity profiles. Abstract : This paper describes the long‐term survival patterns of patients following endovascular and open repair of unruptured abdominal aortic aneurysms. Patients were stratified by age group and co‐morbidity, and a regression method that overcomes the violation of the Cox proportional hazards assumption was used. Long‐term survival varied markedly by patient group. K–M, Kaplan–Meier; EVAR, endovascular aneurysm repair. Marked variation with age and comorbidity Abstract : Antecedentes: El objetivo de este artículo fue examinar los patrones de supervivencia a 10 aáos tras reparación electiva de aneurismas de la aorta abdominal sin rotura ( abdominal aortic aneurysms, AAA) en diferentes grupos de pacientes. Métodos: Se identificaron pacientes sometidos a reparación abierta ( open repair, OR) o reparación endovascular ( endovascular aneurysm repair, EVAR) del aneurisma en el Sistema Nacional de Salud Inglés entre enero de 2006 y diciembre de 2015, a partir de los datos del Hospital Episode Statistics . Se analizaron la supervivencia postoperatoria entre los pacientes de diferentes edades y los perfiles de comorbilidad con la puntuación de Charlson modificada del Royal College of Surgeons of England (RCS) utilizando modelos de supervivencia paramétricos flexibles. También se analizó la relación entre las características de los pacientes y el riesgo de rotura tras la reparación. Resultados: Un total de 37.138 pacientes fueron sometidos a reparaciones electivas de AAA, de las cuales 15.523 fueron reparaciones abiertas y 21.615 endovasculares. La mortalidad a los 10 aáos fue del 38% para los pacientes de edad inferior a los 70 aáos, y las curvas de supervivencia de la OR y EVAR fueron similares cuando los pacientes no tenían comorbilidad con el Charlson modificado del RCS. Entre los pacientes de edad avanzada y aquellos pacientes con comorbilidad, la mortalidad a los 10 aáos aumentó, excediendo el 70% para los pacientes de más de 80 aáos de edad. La media de los tiempos de supervivencia superior a 10 aáos para OR y EVAR fueron similares dentro de los subgrupos de pacientes de edad avanzada y más comorbilidad, pero las curvas de supervivencia se hicieron cada vez más diferentes, con la OR mostrando un mayor riesgo a corto plazo en los primeros 6 meses pero tasas de mortalidad a los 10 aáos más bajas. El riesgo de rotura mas allá de los 9 aáos fue 3, 4% para EVAR y 0, 9% para la reparación abierta, con una débil asociación con los factores inherentes a los pacientes. Conclusión: Los patrones de supervivencia a largo plazo tras OR y EVAR electivas para AAA sin rotura varían notablemente entre pacientes con perfiles de edad y comorbilidad diferentes.